Resource conservation technology for sustainable productivity of intensive rice-based cropping pattern in Bangladesh - Mobarak, Hossain; Mahfuza, Begum; Moshiur, Rahman; Abul, Hashem; Bell, Richard (Peertechz Publications Private Limited, 2021)
Exhaustive conventional tillage and removing residues of previous crops in the rice-based cropping system are labor intensive, costly, soil destructive and non-ecofriendly. In recent years, increased concerns for healthier food production and environmental quality, and increased emphasis on sustaining the productive capacity of soils, have raised concern in the maintenance and improvement of soil organic matter through appropriate land use and management practices. Strip tillage with the application of herbicides and crop residue mulching are being developed to overcome this challenge. A two-year experiment of the summer rice-mustard-winter rice (R-M-R) system was conducted at the farmers’ field in the northern Bangladesh during 2014-2016. Summer rice (BRRI hybrid dhan6), mustard (BARI Mustard 14) and winter rice (BRRI dhan28) were grown under, T1: Conventional tillage (CT) + three hand weeding (Control) and T2: Pre-plant herbicide (PRE) + strip tillage (ST) + pre-emergence herbicide (PE) + post-emergence herbicide (PO) with two levels of crop residue mulching, M0: no-mulch and M50: 50% standing mulch. The CT consisted of two primary tillage operations by a two-wheel tractor, and ST had done by a Versatile Multi-crop Planter in a single-pass process. The PRE (glyphosate) and PE (pendimethalin) in all crops and the PO (ethoxysulfuron-ethyl in rice and isoproturon in mustard) were applied at recommended dose and time. The combination of applied PRE, ST, followed by PE and PO herbicide and the retention of 50% mulch fetched the highest yield and economic returns of individual crop and the productivity of the summer rice-mustard-winter rice system.